Biodegradation Of Waste Cooking Oil And Waste Engine Oil By Locally Isolated Microfungus, Aspergillus Spp. USM-Ar1 - Jasme, Nurshafiqah (2022)
Large amounts of waste cooking oil and waste engine oil from residential areas and automotive industry, respectively, can impose adverse impact if not disposed off properly. Fungi have a higher tolerance to hydrocarbon toxicity due to their physiology and adaptation to the environment, subsequently equipped with the mechanism for oil utilisation. Therefore, bioremediation using fungi can be employed for waste oil reduction in the environment. In the present study, a filamentous fungus was isolated from used charcoal coated with animal fats, identified morphologically as Aspergillus sp. USM-AR1. The highest oil removal and fungal biomass of waste cooking oil in shake flasks obtained were 81.93 ± 14.22% and 81.67 ± 11.08 g/L, respectively at 144 h in a medium containing 9.83% (v/v) waste cooking oil, 1 g/L ammonium nitrate, 16.32% (v/v) NaCl, 10% (v/v) inoculum concentration and with the initial pH of 8.32 after optimisation studies.